PEMAHAMAN DAN PERSEPSI MASYARAKAT TERHADA KEGIATAN REDD+ DI KPHP TASIK BESAR SERKAP - Sadjati, Emy (Fakultas Kehutanan Universitas Lancang Kuning, 2016)
The research objective was to determine the level of understanding and perception of forest communities against carbon trading and determine the factors that influence the understanding and perception of forest communities on carbon trading. The experiment was conducted for six months (February 2015 -July 2015), involving 60 respondents from community leaders and ordinary citizens from four villages namely Sungai Rawa village, Rawa Mekar Jaya village, Penyengat village and Teluk Lanus village in the region Sungai Apit district of Siak, Province Riau with a survey method that is divided into two activities: (1) Focus Group Discussion (FGD), and (2) structured interviews with villagers. The study states that the majority of respondents (58.49%) stated that they had never heard of the term climate change / REDD / carbon trading. The majority of respondents (50.00%) did not give an answer on the form of institutions that have the potential to implement carbon trading activities, while other respondents (12.50%) expressed the need for training for members of the institution designated to implement the REDD + activities. Understanding of society remains low and the perception of the public is still in doubt with this activity becau se it has not seen examples of activities that have been successful. Factors associated with a real understanding in relation to carbon trading activities are education and perception. Results of other studies conclude that there is a significant correlation between education and perception.